The Influence of Transformational Leadership, Competence, and Placement on Job Satisfaction of Employees of the East Java Province Pamong Praja Police Unit - Vadilla, Icha Tyas Nur; Santoso, Bowo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the effect of transformational leadership, competence, and placement on the job satisfaction of employees of the East Java Province Pamong Praja Police Unit. This type of research is quantitative research. The object of this research is the employees of the East Java Province Civil Service Police Unit. The sample in this research was 83 respondents. The data analysis technique used is Partial Least Square (PLS). The data analysis process is assisted by the SmartPLS software program. The result of this research indicates that transformational leadership contributes to job satisfaction, competence does not contribute to job satisfaction and placement contributes to the job satisfaction of employees of the East Java Province Civil Service Police Unit. Overall, transformational leadership, competence, and placement variables together have an influence of 78.1% on job satisfaction.